Coral reef fishes in the coastal waters of Ninh Thuan province - Dat, Mai Xuan; Long, Nguyen Van; Hong, Phan Thi Kim (Vietnam Journal of Marine Science and Technology, 2021)
This study was conducted to evaluate the species composition and distribution of coral reef fish communities at 24 sites in three areas Ninh Hai, Phuoc Dinh, and Ca Na in Ninh Thuan province from 2018 to 2019. A total of 301 species belonging to 131 genera and 49 families of coral reef fishes were recorded. Among them, the wrasse (Labridae: 55 species), the damselfish (Pomacentridae: 46 species) and the butterflyfish (Chaetodontidae: 26 species) occupy the three highest proportion. The average density of coral reef fish in coastal waters of Ninh Thuan province is 106.8 ± 23.4 individuals/100 m2, most of them are small sized fish and ornamental fish groups. Ninh Hai has a higher species richness and density than other areas. Meanwhile, Ca Na and Phuoc Dinh have the two highest densities of the large sized fish and food target fish groups. This research also points out the impact of monsoon on the density and distribution of coral reef fish, in which Ninh Hai is most affected.